Risk of infections, chronic diseases and mental health disorders after Floods by the Coastal Child Phenomenon in displaced populations, Piura, 2017: Riesgo de infecciones, enfermedades crónicas y trastornos de salud mental con posteridad a inundaciones por el Fenómeno del Niño Costero en poblaciones desplazadas, Piura, 2017 - Loayza-Alarico, Manuel J. (2021)
Introduction: In Peru, the presence of the Coastal Child Phenomenon produces floods and the appearance of diseases cyclically. Objective: To determine the risk factors for the presence of diseases in displaced populations in Piura due to the Nino Costero. Methods: Quantitative, longitudinal, analytical investigation of cases and controls with 544 families that were selected through a two-stage random sampling considering the proportion of families per block, area and cluster. For data collection, various diagnostic and monitoring instruments were used, such as that of the International Organization for Migration (IOM), the health care base and the application of an instrument for mental health. Results: The analysis of the variation of care in two time periods at 3 and 9 months shows that there are statistically significant changes in these periods that include skin infections, urinary tract infection, joint pain, diabetes mellitus and family violence. 26.46% presented some psychological disorder associated with coexistence in shelters. The bivariate analysis showed that families with less than 80% of safe water management and safe water storage were at risk of presenting acute diarrheal diseases with OR = 6.15 (95% CI 5.97-6.95) and OR = 2.08 (95% CI 1.06- 2.97) respectively. Conclusions: The epidemiological profiles show the presence of psychological effects and the transition of communicable diseases at the beginning of the disaster and that over time, non-communicable diseases and violence appear in the shelters associated with the previous health profiles of the displaced population.